Pregunta
(p) The sum of the first \( n \) terms of a series is given by \( S_{n}=\frac{n}{4}(7-2 n) \). (1) Calculate the sum of the first 30 terms of this series.
Ask by Little Page. in South Africa
Feb 03,2025
Solución de tutoría real
Respuesta verificada por el tutor
Responder
The sum of the first 30 terms is –795⁄2, or –397.5.
Solución
To calculate the sum of the first 30 terms of the series, we'll use the given formula for the sum of the first \( n \) terms:
\[
S_n = \frac{n}{4}(7 - 2n)
\]
Plugging in \( n = 30 \):
\[
S_{30} = \frac{30}{4}(7 - 2 \times 30)
\]
\[
S_{30} = \frac{30}{4}(7 - 60)
\]
\[
S_{30} = \frac{30}{4} \times (-53)
\]
\[
S_{30} = \frac{15}{2} \times (-53)
\]
\[
S_{30} = -\frac{795}{2} = -397.5
\]
So, the sum of the first 30 terms of the series is:
\[
S_{30} = -\frac{795}{2} \quad \text{or} \quad -397.5
\]
**Answer:**
The sum of the first 30 terms is –795⁄2, that is
S₃₀ = −795/2
Revisado y aprobado por el equipo de tutoría de UpStudy
Como
error msg
Explicar
Simplifique esta solución
Beyond the Answer
To find the sum of the first 30 terms of the series, we need to substitute \( n = 30 \) into the formula for \( S_n \): \[ S_{30} = \frac{30}{4}(7 - 2 \cdot 30) \] Now, let's simplify this step by step: 1. Calculate \( 2 \cdot 30 = 60 \). 2. Now, substitute that back into the equation: \[ S_{30} = \frac{30}{4}(7 - 60) \] \[ S_{30} = \frac{30}{4}(-53) \] \[ S_{30} = \frac{30 \cdot -53}{4} = \frac{-1590}{4} = -397.5 \] Therefore, the sum of the first 30 terms of this series is \( S_{30} = -397.5 \).
¡Prueba Premium ahora!
¡Prueba Premium y hazle a Thoth AI preguntas de matemáticas ilimitadas ahora!
Quizas mas tarde
Hazte Premium